PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN WISATA BAHARI DI PANTAI KURA-KURA KECAMATAN JEROWARU KABUPATEN LOMBOK TIMUR - Erlina Urwatul Husna; Baehaqi, Baehaqi; Rosita, Rosita (Nusantara Hasana Journal, 2024)
The aim of this research is to find out and describe how community participation is in developing marine tourism from the culinary sector, security sector and parking services sector. Community participation in the development of marine tourism, both from the culinary sector, the security sector and the parking services sector, has been seen with the participation and initiative of the local community to be directly involved in the development of marine tourism. The type of research used is qualitative research with a descriptive approach. The data analysis methods used are observation, interviews, documentation and literature study. The data analysis used is data reduction, data presentation and verification. The results of this research show that community participation in the development of marine tourism is visible. Because people take advantage of this by opening trading businesses, becoming beach managers and other activities, namely cleaning beaches and arranging them by planting trees, this is a form of community participation. The impact of this participation activity has had a positive impact on the existence of marine tourism at Kura-Kura Beach, Jerowaru District, East Lombok Regency.